A Study on the Propensity to cheat in University Exams: Development and Validation Process of the Questionnaire on Cheating in University Exams (QCUE) - Eric Frenette; Sylvie Fontaine; Marie-Hélène Hébert; Mikhaël Éthier (Mesure et Évaluation en Éducation, 2019)
This paper presents the seven-step approach to maximizing the evidence of validity that led to the development of the Questionnaire sur la tricherie aux examens à l’université (QTEU) [Questionnaire on Cheating in University Exams (QCUE)]. Composed of 28 items divided into 7 factors (propensity to cheat in exams, peer influence, cheating methods, institutional context, perception of control, performance goal, and commitment to one’s studies), the QCUE design was based on a comprehensive conceptual analysis of the scientific literature on cheating in exams, and on the work of Frenette, Hébert, Thibodeau, and Ndinga (2018) on how to develop a questionnaire maximizing the accumulation of validity evidence. With good psychometric properties, the QCUE meets a need for a French-language questionnaire on the propensity to cheat in exams and allows to measure the scope of cheating among university students.